Online Education: Before, During, and After - Scott, Chyllis Elayne; Jackson, Morgan (Selangor Humaniora Review, 2022)
When the world shutdown in March 2020 due to the global COVID-19 pandemic, the world was forever changed. One major change that impacted billions was the delivery of education and the types and modes of instruction. As educators we were impacted firsthand by these changes and see the ongoing effects in our teachers and students. In this paper, we continue to the conversation about education, specifically discussing the limitations and advantages of online learning.